Impact Analysis Before and After the Implementation of PSAK 72 on the Company's Financial Performance in Real Estate Companies on the Indonesia Stock Exchange in 2018-2021: Analisis Dampak Sebelum dan Sesudah Penerapan PSAK 72 Terhadap Kinerja Keuangan Perusahaan pada Perusahaan Real Estate di Bursa Efek Indonesia Tahun 2018-2021 - Atho, Ibnu Athoillah; Rahayu, Duwi (Universitas Muhammadiyah Sidoarjo, 2022)
Considering the Covid 19 pandemic, a significant number of which have redirected a portion of their assets towards wellbeing so the property area has an extremely enormous effect. This study expects to analyze the effect later and before the utilization of PSAK 72 on the organization's monetary execution in land property area organizations recorded on the IDX. In this study utilizing quantitative strategies through SPSS information handling devices, testing in view of models or purposive examining so there are 31 organizations chosen and contained in foreordained rules so estimations are completed in light of arrangement of the information got. As per the examination results, it is found: There is no distinction in the organization's monetary execution when the utilization of PSAK 72 which is proxied by the Current Ratio and Debt To Asset Ratio then there are contrasts in the organization's monetary execution when the use of PSAK 72 which is proxied by Net Profit Margin.